2005
DOI: 10.1111/j.1365-2672.2004.02450.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization, technological properties and safety aspects of enterococci from 'Hussuwa', an African fermented sorghum product

Abstract: Aims: To identify enterococci from Hussuwa, a Sudanese fermented sorghum product, and determine their technological properties and safety for possible inclusion in a starter culture preparation. Methods and Results: Twenty-two Enterococcus isolates from Hussuwa were identified as Enterococcus faecium by using phenotypic and genotypic tests such as 16S rDNA gene sequencing, RAPD-PCR and restriction fragment length polymorphism of the 16S/23S intergenic spacer region fingerprinting. Genotyping revealed that stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 46 publications
6
36
0
1
Order By: Relevance
“…The exact role of efaAfm as a virulence factor is still unknown (11). The efaAfm gene has not yet been conclusively shown to contribute to pathogenesis in animal studies, in contrast to the adhesion-like E. faecalis antigen A (efaAfs) (15). Furthermore, the absence of cylMBA and gelE genes in E. faecium EYT17, EYT31, and EYT39 strains agrees with our observation that these strains lack β-haemolytic and gelatinase activity.…”
Section: Detection Of Virulence Genessupporting
confidence: 79%
See 1 more Smart Citation
“…The exact role of efaAfm as a virulence factor is still unknown (11). The efaAfm gene has not yet been conclusively shown to contribute to pathogenesis in animal studies, in contrast to the adhesion-like E. faecalis antigen A (efaAfs) (15). Furthermore, the absence of cylMBA and gelE genes in E. faecium EYT17, EYT31, and EYT39 strains agrees with our observation that these strains lack β-haemolytic and gelatinase activity.…”
Section: Detection Of Virulence Genessupporting
confidence: 79%
“…PCR for structural genes of enterocins was performed as an initial cycle of denaturation at 94 °C for 5 min, followed by 35 cycles of denaturation 94 °C for 1 min, annealing at an appropriate temperature for 1 min, and elongation at 72 °C for 40 s (15). The amplification products were analysed by electrophoresis on 1.5% agarose gel at 120 V for 1.5 h in Tris-acetate-EDTA buffer and revealed in ethidium bromide (20 µg/mL).…”
Section: Pcr Detection Of Known Enterocin Genesmentioning
confidence: 99%
“…Similarly Andrighetto et al (2002) analysed the genetic variability within 218 S. thermophilus isolates from Italian traditional cheeses by RAPD-PCR and showed five major clusters at 60% similarity level. Later, Yousif et al (2005) showed considerable degree of genomic diversity between 21 Enterococcus isolates from Hussuwa fermentations carried out in different surroundings by RAPD-PCR genotyping using M13 and AP4 primer. Omar et al(2006) also evaluated the genetic diversity of seven isolates from ben saalga, a traditional fermented gruel from Burkina Faso using primer M13 and AP4, and found that six of the isolates were genetically different, indicating that they were in fact different strains.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, before using enterococci for food production or in probiotic preparations, safety of these strains should be evaluated. Recently, many authors have assessed the safety of enterococci isolated from different origins [93][94][95][96][97]. Safe strains of enterococci that can be used in food and as probiotics ideally should possess neither any of virulence factors, nor should be able to acquire antibiotic resistance gene [8].…”
Section: Safety Assessment Of Enterococcimentioning
confidence: 99%